Enhancing antibiotic production through the genetic engineering of Streptomyces species - Pak, Patricia (My University, 2010)
Antibiotics have a prominent role in the human healthcare system. With natural sources, such as bacteria, acting as the main source of antibiotics, it is no wonder that the actinomycete bacterium Streptomyces coelicolor A3(2) is so prominent in this field of research. Although none of the four known antibiotics it produces have any clinical use, there is a wealth of genetic information and tools available for this model Streptomyces (producers of over two-thirds of the world's antibiotics ).
In recent years, there has been a gradual decline in the discovery of new antimicrobial drugs despite the rising need to combat increasingly resistant strains of bacteria. As such, my work focused on investigating the various methods of antibiotic overproduction available through genetic manipulations. Phenotypic analysis, antibiotic assays, and RT-PCR demonstrated the effectiveness of the ermE* promoter from Saccharopolyspora erythraea, in conjunction with the tufI ribosome-binding site, in the overexpression of the atrA gene in S. lividans. This provided support for the incorporation of both these regulatory elements in an effective heterologous overexpression vector for Streptomyces.
Overexpression of regulator genes as a method of stimulating increased and/or novel antimicrobial compounds is a common endeavor. Here, we investigated the effectiveness of expressing S. coelicolor genes in the Streptomyces wild isolate, Cu#39. Additionally, as a tool for antibiotic research, we created a S. coelicolor strain constructed to direct its metabolic resources towards a designated metabolite. By eliminating select endogenous secondary metabolites, this strain holds the potential of serving as a host for increased yields of heterologous molecule production. In these three projects, I explored the use of Streptomyces as a reservoir for the identification of new antibiotics.
Keywords: Biology; Biology